Fiji Constitution Review Commission, written submissions and verbatim notes. - Fiji. Constitution Review Commission; Reeves, Paul, Sir, 1932-2011.; Lal, Brij V.; Vakatora, Tomasi R.; Australian National University. Pacific Manuscripts Bureau (1995-1996., 1995)
The papers are divided into eight volumes of written submissions from 3 July 1995 to 14 September 1995, with the eighth volume consisting of additional submissions received by the Commission between July 1995 and January 1996. The remainder of the contents consists of verbatim notes resulting from oral submissions made between 3 July 1995 and 19 September 1995.
Microfilm.
Originals held by Professor Brij Lal, Centre for the Contemporary Pacific, RSPAS, Australian National University, Canberra, ACT, 0200, Australia.
Fiji Constitutional Review Commission was established by His Excellency, the President of Fiji, Ratu, Sir Kamasese Mara, on 15 March 1995. He appointed the Right Reverend Sir Paul Reeves as Chairman of the Commission and Mr Tomasi Rayalu Vakatora and Dr Brij Vilash Lal as its other members. Ms Alison Quentin-Baxter and Mr Jon Apted were later appointed as Counsel assisting the Commission along with Mr Walter Gibson Rigamoto as its Secretary. The Commission was appointed to review the Fiji Constitution and produce a report on 30 June 1996 (later extended to 30 September 1996) "recommending constitutional arrangements which will meet the present and future needs of the people of Fiji and promote racial harmony, national unity and the economic and social advancement of all communities" (Reeves, Vakatora and Lal, 1996:2).
The Commission was required to scrutinise the Constitution, facilitate the widest possible debate on constitutional matters and inquire into and ascertain public opinion on possible ways to improve the Constitution. These papers represent the written and oral submissions which individuals, groups and organisations made to the Commission.
Keywords: Fiji -- Constitutional history; Fiji -- Politics and government -- 20th century